UPAYA GURU MENGURANGI PERILAKU MEMUKUL PADA ANAK GANGGUAN PERILAKU DENGAN PENDEKATAN HIGH-TOUCH - Novarina - - (Universitas Negeri Padang, 2014)
This Research was based on the problem related to a boy named as X who was in the fourth grade of SLB Al-Hidayah Padang. He could not control his such behavior as hitting other students without any reasons, uttering dirty words and feeling innocent for his mistake. This research was aimed at diminishing the hitting behavior of a kid with behavioral disorders by using High Touch approach. This was an experimental research which use Single Research Subject (SSR) and applied A-B design. The subject of the research was a boy named as X at SLB Al-Hidayah Padang. He was 14 years old. This research was started from the baseline condition which was the kid’s joy of hitting others, and then it was continued to the intervention condition in which a treatment given to the kid. In order to make the result of the research clear, the data gathered was processed by using graphic. The result of the data analysis showed that in the baseline condition (A) the number of the boy hit his friends was 30 times in 15 minutes while in the intervention condition in which the High-Touch approach was applied, the number was getting smaller. Thus, it was concluded that the use High-Touch approach could diminish the hitting behavior of the kid with behavioral disorders. Therefore, it was suggested to the teacher to apply High-Touch approach to reduce unsolicited behaviors.